Transition Metal Mediated C–H Activation and Functionalization: The Role of Poly(pyrazolyl)borate and Poly(pyrazolyl)alkane Ligands. Issue 15 (12th February 2016) - McKeown, Bradley A.; Lee, John P.; Mei, Jiajun; Cundari, Thomas R.; Gunnoe, T. Brent
Abstract : The emergence of hydridotris(pyrazolyl)borate (Tp) and related ligands has had a substantial influence in the field of organometallic chemistry with regards to C–H activation. The electronic and structural properties of Tp and related ligands, such as poly(pyrazolyl)alkane ligands, play an important role in the ability of several transition metal complexes to mediate C–H activation and functionalization. Herein, several studies of stoichiometric and catalytic C–H activation by platinum group metals are reviewed. Abstract : This microreview presents work surrounding the development and study of Tp‐supported platinum group metal complexes for stoichiometric and catalytic C–H bond activation. From κ 2 ‐ and κ 3 ‐coordination modes to increased sterics to electronic parameters, Tp and related ligands have played an important role in the observed reactivity of Ru, Rh and Pt‐mediated C–H bond activation reactions.